Banjir rescue: IOT-based flood evacuation center / Nor Azimah Khalid ... [et al.] - Khalid, Nor Azimah; Syamsurial, Nur aliah; Mohamed Noor, Noorhayati; Abdullah, Shapina (Universiti Teknologi MARA, 2025)
One of the important processes involved when a disaster happens is to allocate the victims to the navigation center. Current evacuation practices may cause further damage as the victims must wait for the rescue team to come. A self-navigation system, called Banjir Rescue, would allow the victims to save their lives and belongings sooner by determining the appropriate evacuation center. In this approach, the appropriate evacuation center is determined based on two critical parameters, which are the water level and distance. First, the near-real-time data retrieved from the water level sensor set up at the evacuation centers is sent to the system and compared with the evacuation centers' water threshold value. The algorithm will then proceed with the second phase, that is, checking for the distance between the victim’s current location and the evacuation center if the water level found in the first phase is less than the threshold. Finally, the selection is made where the algorithm will choose the nearest evacuation center to the victims. The system will get the coordinates of the appropriate evacuation center that passes both phases and send the coordinates to the installed navigation applications on the mobile phone, such as Google Maps and Waze. The desired navigation app will be launched with the coordinates passed from the system to guide victims to reach the appropriate evacuation center. The result shows that the proposed approach could provide a near-real-time water level reading of each sensor and near-accurate distance calculation to the system to determine the appropriate evacuation center.